Combined techniques of secondary atomization of multi-component droplets. (14th December 2019) - Kuznetsov, G.V.; Shlegel, N.E.; Solomatin, Ya.; Strizhak, P.A.
Graphical abstract: Highlights: Combined techniques provide an over 10–15-fold decrease in droplets sizes. Free liquid surface area can be increased 40–50 times. Homogeneous drops are intensively crushed during collisions with walls and drops. Micro-explosive atomization is more effective for multi-component droplets. Experimental results are generalized using two initial droplets and an aerosol. Abstract: In this paper, we present the experimental results of a secondary droplet atomization study by combining four schemes: droplet collisions with each other, with a solid surface, with a gas flow, as well as micro-explosive breakup of highly inhomogeneous liquid exposed to extensive heating. For each of the four schemes, we show the droplets sizes reduction range, atomization time, and the measured growth of liquid surface area. The latter parameter describes the intensity of the heat exchange and phase transitions at the liquid – gas interface. The experiments are conducted for water and water-based slurries and emulsions, including high-potential fuels. Basing on the experimental results for isolated droplets, we propose a technique for the experimental study of aerosol flows. We determine the droplets sizes that does not lead to its drastic increase due to coalescence or decrease due to disruption during aerosol cloud intermixing.